Small planet in the vastness of space: Globalization and the proliferation of UFOs, aliens, and extraterrestrial threats to humanity - John Boli (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
Globalization entails conceiving the world as a single social unit whose boundary encompasses the entire globe. Beyond the boundary lies the Outside, which becomes the object of increasing attention as globalization intensifies. Since the late 19th century, and above all since the mid-20th century, numerous forms of cultural production have arisen to fill the great void of the Outside, including astronomy and astrophysics - which helped demarcate the boundary initially - and a wide variety of imaginative cultural spheres: observer reports of UFO sightings; crop circle formations attributed to extraterrestrials; tales of alien abductions; books, films, newspaper articles, video games, and doctoral dissertations about alien life and alien invasions. I use yearly data regarding these types of cultural production during the recent period of intensifying globalization (mostly since the 1940s) to test four hypotheses about globalization and the Outside: (1) that such cultural production increases with globalization, (2) that it declines during major disruptions in world society, (3) that some forms of such cultural production may be fads that decline even as globalization intensifies, and (4) based on a Durkheimian argument, that cultural production regarding the nature of aliens in close encounters strongly favors humanoid forms. The results generally support the hypotheses, with most cultural production forms according with the first two hypotheses and only crop circle production displaying a faddish form. – – Das Konzept der Globalisierung beinhaltet das Verständnis der Welt als einzelne soziale Einheit, deren Grenzen den gesamten Globus umfassen. Hinter diesen Grenzen liegt das "Unbekannte", welches mit voranschreitender Globalisierung immer mehr zum Objekt des Interesses wird. Spätestens seit dem späten 19. Jahrhundert, vor allem aber seit Mitte des 20. Jahrhunderts, sind zahlreiche kulturelle Produktionen entstanden, die es sich zur Aufgabe gemacht haben, die Leere des "Unbekannten" zu füllen. Dazu gehören Astronomie und Astrophysik, die die ursprünglichen Grenzen aufzeigten, sowie eine Vielzahl anderer Bereiche: Beobachter berichten von Ufo-Sichtungen; Kornkreise, die mit Außerirdischen in Verbindung gebracht werden; Geschichten von Entführungen durch Aliens; Bücher; Filme, Zeitungsartikel, Videospiele und Dissertationen über außerirdisches Leben und Invasionen durch Aliens. Ich verwende Daten, die diese Arten kultureller Bereiche während der jüngsten Phase der Globalisierung (seit den 1940er Jahren) abbilden, um vier Hypothesen über Globalisierung und das "Unbekannte" zu testen. (1) Die o.g. kulturellen Produktionen vermehren sich im Zuge der Globalisierung. (2) Sie schrumpfen während negativer Ereignisse in der Weltgesellschaft. (3) Manche der kulturellen Produktionen treten nur kurzzeitig auf und schrumpfen, obwohl sich der Globalisierungsprozess intensiviert. (4) Ausgehend von einem Durkheim'schen Argument, favorisieren kulturelle Produktionen, die sich mit der Natur von Aliens befassen, menschenähnliche Formen. Die Ergebnisse liefern empirische Unterstützung für die Hypothesen, wobei die meisten Formen kultureller Produktionen mit den ersten beiden Hypothesen übereinstimmen und lediglich die Ergebnisse zu Kornkreis-Produktionen schwankender sind.
Keywords: 320; Globalization; UFOs; Extraterrestrial Threats